ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN UTANG, ROA DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN: STUDI 1995-1996 - Nuringsih, Kartika (Jurnal Akuntansi dan Keuangan Indonesia, 2005)
This research examined the influence of managerial ownership, debt policy, ROA andfirm size on dividend policy. Actually under dividend policy still have many puzzles. The research model is developed from Chen & Steiner (1999), Moh ’d, Rimbey & Perry (1995), Jensen, Solberg and Zorn (1992), Chrutchley & Hansen (1989), with focusing at 60 samples from manufacturing company. Data are taken from Indonesia Capital Market Directory in 1995-1996. It uses 3 equations, the first is multiple regressions for examining four hypothesis. The results show: managerial ownership is positive and significant to dividend policy, debt policy is negative and significant to dividend policy, ROA is negative and significant to dividend policy, andfirm size is positive but is not significant to dividend policy. The second and third are simple regressions for analyzing two grouped of managerial ownership. The results show that the low rate of managerial ownership and the high rate of managerial ownership are positive relation on dividend policy. The results don 't prove the different of linier relation between managerial ownership and dividend policy.